العقدة الدرقية: تشخيص وعلاج - قنجراوي أكثم; علي ماجد; ناصر أحمد (Latakia University Journal -Medical Sciences Series, 2019)
اشتملت الدراسة على 288 مريضاً لديهم عقد درقية راجعوا قسم الجراحة في مشفى الأسد الجامعي باللاذقية بين عامي 2000-2007. قسمت الدراسة إلى: استرجاعية (163 مريضاً) واستقبالية (125 مريضاً), شكّلت الإناث غالبية المرضى: 243 أنثى (84.38%), 45 ذكراًًً (15.63%). معظم المرضى في العقد الرابع من العمر. الغالبية العظمى من العقد كانت حميدة (111) من أصل 125 أي بنسبة (88.8%) وقد سجلت 14 حالة سرطان درق بنسبة (11.2%). تم إجراء التصوير بالأمواج فوق الصوتية لجميع المرضى حيث إنّ معظم العقد كانت صلبة (60.4%), أُجريت FNA لجميع مرضى الدراسة الاستقبالية (125 مريضاً) بحساسية 91.7%, وهكذا فإن هذا الإجراء لديه مصداقية عالية في تشخيص العقد الدرقية وبالتالي في التدبير المناسب. أُجريت الجراحة لـ273 مريضاً، وشكّل الدراق العقيدي معظم استطبابات الجراحة, تم اتباع طرق مختلفة من التكنيك الجراحي. The study included 288 patients with thyroid nodules, who had been accepted in Assad University Hospital in Lattakia (surgery unit) in 2000-2007. The study was divided into: retrospective (163patients), prospective (125patients). Most patients were females (243) (84.38%), males (45) (15.63%). The majority was in the fourth decade of age. Most of nodules were benign (111 of 125)(88.8%), 14 cases recorded as thyroid cancer. Thyroid Ultrasound had been performed on all patients. Most of nodules were solid (60.4%), Fine-Needle Aspiration (FNA) was done for all patients of the prospective study, it had sensitivity (91.7%). So this procedure had high reliability for the diagnosis of thyroid nodules and is also suitable for the management. (273) patients underwent surgery, nodular goiter made most indications, different methods of technique were done.